PERAN KOMUNIKASI ORGANISASI MELALUI NEW MEDIA DALAM MENUNJANG KEGIATAN OPERASIONAL DI PT NATLAS REKARTHA INDONESIA - Josephine Ayu Graciaputri Josephine; Murtiadi; Andi Banus Achir (STKIP Subang, 2026)
This study aims to determine the role of organizational communication through newmedia in supporting operational activities at PT Natlas Rekartha Indonesia. This heavy equipment tire distributor has a geographically separated work structure between its head office in Jakarta and its operational unit in Kalimantan. This research employs a constructivist paradigm with a descriptive qualitative approach through a field study. Data was collected through in-depth interviews with three key informants, there are the Managing Director, the Jakarta Head of Operations, and the Banjarmasin Head of Operations; supported by observation and documentation. The results show that the company utilizes three complementary new media platforms: WhatsApp for rapid daily coordination, email for formal communication and documentation, and Google Meet for cross-regional synchronous virtual meetings. The use of these platforms has positively impacted communication speed, time and cost efficiency, and ease of coordination. Nevertheless, several obstacles were identified, including potential miscommunication due to brief text messages, limited nonverbal communication, information overload on WhatsApp, and unstable internet connectivity in Kalimantan. In conclusion, new media-based communication within the company operates quite effectively in supporting its operations, yet it requires more optimal management to minimize existing barriers.